Children Are the Future of the Nation (With Reference to National Family Health Survey [NFHS] Round 3 and 4 I.E. 2005-06 and 2015-16) - Matkar, Rituparna; Iyer, Malati; Gaikwad, Vishal; Deshmukh, Akash (European Scientific Journal, ESJ, 2017)
The interstate variation in IMR and CMR is the focus of the study and researchers plan to investigate reasons behind the same in India. The selection of three Indian states for the study is based on the planning commission data showing regional disparities in IMR and CMR. The NFHS round 3 and 4 supported in understand various linkages and relationships between various variables. Extensive breast feeding is not directly linked with the rise or fall in Infant Mortality Rate (IMR) and Child Mortality Rate (CMR). Other important factors like women literacy and development of the state play an important role. During the process of finding correlation between IMR, CMR and various factors affecting them, showed rising tendencies of IMR, CMR in those are areas which are economically backward, having illiteracy among women, lack of adequate diet for mother and child etc. The limitation of the study is the source of data as the NFHS round 4 phase 2 is yet to be published while there hasn’t been any research in the same field. The findings of the study are important for various stakeholders of the society so as to contribute towards the human capital development of the nation.